Phenological, postharvest physicochemical and ultrastructural characteristics of Torch Ginger (Etlingera elatior (Jack) R.M. Smith) inflorescence as a cut flower - Choon, Sea Yeat (2016)
The extravagant and showy inflorescence of torch ginger (Etlingera elatior) with bright colour is suitable to be used as a cut flower. The major weakness of this inflorescence is bract browning that shortens its vase life and reduces marketability. The causes of the bract browning disorder and the timing of its occurrence have not been investigated in detail. Understanding the characteristics of torch ginger and the mechanisms that regulate bract browning is needed for the production of high quality inflorescence. The objective of this work was to assess the potential of torch ginger inflorescence as a cut flower. In study one, the growth and development cycle of torch ginger plant was determined. Results showed that the growth and development cycle of torch ginger plants was divided into vegetative and reproductive phases. The entire inflorescence development period took about 60 days from the inflorescence shoot emergence until blooming stage. In study two, the mechanisms of bract opening and peduncle strength of inflorescence was elucidated. The experiment was conducted in a nested design. Data were analysed using general linear model. The means comparison was performed using Tukey's test. Results showed that fresh weight and respiration rate of inflorescence increased gradually from tight bud to bloom stage. The significant higher respiration rate of inflorescence at bloom stage was coincided with a drastic decrease in soluble sugar content in involucral. This result indicates that soluble sugars depletion is the cause of bract browning. As the inflorescence developed, the cellulose content in involucral and floral bracts decreased significantly. In involucral, the cellulase activity showed a significant increase from tight bud to 6-tip opens stage and decreased thereafter. A significant increase in pectin methylesterase activity was recorded from 6-tip opens to torch shows stage in involucral. In peduncle, the ethanol insoluble residue and cellulose content increased significantly from tight bud to bloom stage. In study three, postharvest performance of inflorescences supplemented with sucrose was evaluated. The experiment was conducted in a randomized complete block design with factorial arrangement. Data were analysed using analysis of variance. There was a significant quadratic relationship (P<0.05) between vase life and sucrose concentrations on inflorescences at torch shows stage. The vase life of inflorescences increased quadratically from 0 to 4% sucrose solutions and decreased thereafter. The changes of fresh weight in inflorescences were positively correlated with vase life (r=0.67). The excessive water loss via transpiration in bract cells is the main factor in reducing vase life. Further study should be conducted to reduce the transpiration rate of inflorescence in order to prolong its longevity.